(NpROIZWEDENIQ (B1932-1944 (NGODOW (B/s (N~ASTX (B4s - (NpRI[WIN(B, (NmIHAILs ((NmOSKWA(B:s (NhUDOVESTWENNAQ LITERATURA(B,s, 1983)
(N~ETWERTYJ TOM sOBRANIQ SO^INENIJ m(B.(Nm(B. (NpRI[WINA SOSTAWILI PROIZWEDENIQ(B, (NSOZDANNYE PISATELEM W (B1932-1944 (NGG(B. : (NPOWESTI (B"(NvENX(B-(N{ENX(B", "(NsERAQ sOWA(B", "(NnEODETAQ WESNA(B", (NRASSKAZY DLQ DETEJ I O^ERKI(B.s
rus
Keywords: (NpOWESTI I RASSKAZYs